Cover Picture: Tuning Selectivity and Sensitivity of Mixed‐polymeric Tetraruthenated Metalloporphyrins Modified Electrodes as Voltammetric Sensors of Chloramphenicol (Electroanalysis 4/2019). Issue 4 (11th April 2019) - Ferreira, Luís Marcos Cerdeira; Martins, Paulo Roberto; Araki, Koiti; Angnes, Lúcio
Abstract : This cover picture shows a radio device as analogy for an electrochemical analysis. The device comprises two dials associated to Nickel and Cobalt porphyrins, in which it is possible to tune sensitivity and selectivity. The radio marker shows a cursor with the percentage of amount of the two different porphyrins applied for the composition of different modified electrode films. At the top of the device is shown the possible resulting voltammograms set for the selected tuning. In the blue background is shown the analyte chemical structure, chloramphenicol, as watermark. More details are discussed in the article by Luís Marcos Cerdeira Ferreira, Paulo Roberto Martins, Koiti Araki, and Lúcio Angnes. DOI:10.1002/elan.201800729